2007
DOI: 10.1093/imrn/rnm086
|View full text |Cite
|
Sign up to set email alerts
|

Operator-valued Semicircular Elements: Solving A Quadratic Matrix Equation with Positivity Constraints

Abstract: Abstract. We show that the quadratic matrix equation V W + η(W )W = I, for given V with positive real part and given analytic mapping η with some positivity preserving properties, has exactly one solution W with positive real part. Also we provide and compare numerical algorithms based on the iteration underlying our proofs.This work bears on operator-valued free probability theory, in particular on the determination of the asymptotic eigenvalue distribution of band or block random matrices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
141
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(144 citation statements)
references
References 11 publications
3
141
0
Order By: Relevance
“…The choice of the correct metric on this space follows naturally from the general theory by Earle and Hamilton [17]. The same line of reasoning has appeared before in a context close to ours in [21,26,27].…”
Section: A Existence and Uniquenessmentioning
confidence: 55%
“…The choice of the correct metric on this space follows naturally from the general theory by Earle and Hamilton [17]. The same line of reasoning has appeared before in a context close to ours in [21,26,27].…”
Section: A Existence and Uniquenessmentioning
confidence: 55%
“…The question of existence and uniqueness of solutions to (2.2) with the constraint (2.3) has been answered in [38]. The MDE has a unique solution matrix M(ζ ) for any spectral parameter ζ ∈ H and these matrices constitute a holomorphic function M : H → C N ×N .…”
Section: Note That In Particular S Commutes With Taking the Adjoint mentioning
confidence: 99%
“…Let H = (h x,y ) N x,y=1 ∈ C N ×N be a self-adjoint random matrix. For a spectral parameter ζ ∈ H we consider the associated Matrix Dyson Equation (2.20) preserves the cone C + of positive semidefinite matrices and the MDE therefore has a unique solution [38] whose properties have been presented in Sect. 2.1.…”
Section: Random Matrices With Correlationsmentioning
confidence: 99%
“…In [12], this convolution is analyzed in great detail: among others, a formula for the density of the corresponding distribution is provided, and it is shown that this density is bounded, continuous and analytic wherever positive. However, in order to study the asymptotic eigenvalue distribution of more general selfadjoint polynomials P (A N , H N ) it is necessary to consider the more general framework of free convolutions of operator-valued distributions [27,22,23,17,5]. In the present note, we find certain operator-valued counterparts of Biane's results from [12]; necessarily, several of the conclusions of [12] do not hold in this more general setting.…”
Section: Introductionmentioning
confidence: 69%